Physical exercise is a non-pharmacological method to manage asthma in peoples with asthma: Systematic review - Muhabaw Zewde; Kefelegn Zenebe (Turkish Journal of Kinesiology)
Asthma is a chronic inflammatory disease of the airways that affects over 250 million people worldwide and is responsible for approximately 455,000 deaths annually. Characterized by variable expiratory flow and respiratory symptoms such as persistent cough, wheezing, shortness of breath, and chest tightness, asthma can significantly hinder daily activities and quality of life. While pharmacological treatments are essential for managing asthma, non-pharmacological interventions, including physical activity, nutritional changes, and psychological support, play a crucial role in alleviating symptoms and enhancing overall well-being. Aerobic training, in particular, has been shown to provide health benefits that are dose-dependent, improving the quality of life for asthma patients. Despite the potential benefits of physical activity, individuals with asthma may experience exercise-induced bronchoconstriction, which can trigger symptoms during exertion. Historically, patients were advised to avoid exercise; however, recent studies suggest that regular exercise can improve fitness levels and reduce exacerbations in asthmatics. This review highlights the importance of integrating structured physical activity into asthma management strategies for peoples who often face challenges related to obesity and inadequate asthma control. Regular moderate-intensity aerobic exercise can enhance lung function, improve asthma control, oxygen uptake, immune function, antioxidant capacity, and reduce septum eosinophil and fractional exhaled nitric oxide and promote social engagement, making it essential for asthmatics to remain active. Individuals with asthma can participate in exercises like those without the condition, aiming for 20-30 minutes of activity 2-3 days a week. It's important to consult a healthcare provider before starting any exercise program and to use beta-2 agonists if experiencing exercise-induced bronchoconstriction.